Evaluation of Occupational Safety and Health Implementation on Employee Performance in Limestone Mining Operations - Pratama Sandi Alala; Afdi Dama Zafrila; Ayu Setyaning Sayekti Poesoko (Jurnal Teknologi dan Manajemen, 2027)
Occupational Safety and Health (OSH) plays a strategic role in improving operational performance in mining industries due to the high level of occupational hazards associated with mining activities. This study evaluates the implementation of Occupational Safety and Health (OSH) practices and their influence on employee performance at PT. Sinar Asia Fortuna, a limestone mining company located in Rembang Regency, Central Java, Indonesia. A mixed-method approach combining qualitative observation and quantitative analysis was employed. Primary data were collected through field observations, interviews, and structured questionnaires distributed to employees. The quantitative data were analyzed using validity testing, multiple linear regression, coefficient of determination, and analysis of variance (ANOVA). The findings indicate that several unsafe behaviors are still observed in mining activities, particularly the inconsistent use of personal protective equipment (PPE), inadequate supervision, and limited employee awareness regarding occupational safety procedures. Regression analysis demonstrates that occupational safety implementation significantly influences employee performance, although behavioral compliance remains the dominant factor affecting the effectiveness of the safety management system. Improving safety culture through continuous supervision, periodic training, and stronger enforcement of safety regulations is expected to reduce workplace risks while enhancing employee productivity. The study provides practical recommendations for strengthening safety management systems in surface limestone mining operations.